An atlas on the comparative anatomy of the retinae of vertebrates - Yew, D. T. W. (David T. W.) (Bentham Science Publishers, 2012)
"This atlas covers basic as well as novel information on the retinae of various representative vertebrates including fish, amphibians, reptiles, birds, and mammals. The book consists of over 200 illustrations with brief descriptions pointing out special features of each retina displayed. The detailed information on the complexity and variety of visual cells in different animals will give interested readers an insight on the retinae of vertebrates. The book is divided into the following sections: 1) the general architecture of retinae in different groups of animals; 2) the types of visual cells in different vertebrates; 3) the other retinal cells and synapses; 4) the degenerating retina; 5) general format of vertebrate retinal development. This atlas provides a sufficient framework in comparative retinal studies to inspire new research in the field of functional ophthalmology and biodiversity of visual cells. The book should be a useful reference for biologists, veterinarians, ophthalmologists, and eye researchers."--